Regulation of Ergosterol Biosynthesis in Pathogenic Fungi: Opportunities for Therapeutic Development - Lingyun Song; Sha Wang; Hang Zou; Xiaokang Yi; Shihan Jia; Rongpeng Li; Jinxing Song (Microorganisms)
Ergosterol plays a dual role in fungal pathogenesis and azole resistance, driving key advancements in the understanding of its biosynthesis regulation. This review integrates the latest research progress on the regulation of fungal ergosterol biosynthesis and its role in drug resistance and pathogenicity. We comprehensively discuss the functions of key enzymes (such as Erg11p/Cyp51A, Erg6p, Erg3p, and Erg25p) in the mevalonate, late, and alternative pathways. Notably, we highlight the complex regulation of cyp51A expression by factors such as SrbA, AtrR, CBC, HapX, and NCT in Aspergillus fumigatus, and elucidate the distinctive roles of Upc2, Adr1, and Rpn4 in Candida species. Importantly, we summarize recent discoveries on the CprA-dependent regulation of Cyp51A/Erg11p and heme-mediated stability control. Based on these findings, we propose innovative antifungal strategies, including dual-target inhibition and multi-enzyme inhibition by natural products, which provide novel insights and potential directions for the development of next-generation antifungal therapies.